2016
DOI: 10.5465/amj.2014.0850
|View full text |Cite
|
Sign up to set email alerts
|

Engaged and Productive Misfits: How Job Crafting and Leisure Activity Mitigate the Negative Effects of Value Incongruence

Abstract: The work life of "misfits"-employees whose important values are incongruent with the values of their organization-represents an under-researched area of the personenvironment fit literature. The unfortunate reality is that these individuals are likely to be disengaged and unproductive at work. In this manuscript, we entertain the possibility that employees can protect themselves from this situation if they engage in alternative actions that supplement the fundamental needs that go unmet from value incongruence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
242
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(249 citation statements)
references
References 82 publications
4
242
1
2
Order By: Relevance
“…This method was used to account for the asymmetric sampling distribution of the indirect effect (Preacher, Zyphur, & Zhang, ). To improve the statistical power, we also followed previous studies (e.g., Kearney & Gebert, ; Y. Liu et al., ; Preacher et al., ; Uy, Lin, & Ilies, ; Vogel, Rodell, & Lynch, ) to use 90% CIs to test mediation and moderated mediation in multilevel modeling, as our hypotheses were directional and theory‐driven.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was used to account for the asymmetric sampling distribution of the indirect effect (Preacher, Zyphur, & Zhang, ). To improve the statistical power, we also followed previous studies (e.g., Kearney & Gebert, ; Y. Liu et al., ; Preacher et al., ; Uy, Lin, & Ilies, ; Vogel, Rodell, & Lynch, ) to use 90% CIs to test mediation and moderated mediation in multilevel modeling, as our hypotheses were directional and theory‐driven.…”
Section: Methodsmentioning
confidence: 99%
“…To improve the statistical power, we also followed previous studies (e.g., Kearney & Gebert, 2009;Y. Liu et al, 2015;Preacher et al, 2010;Uy, Lin, & Ilies, 2016;Vogel, Rodell, & Lynch, 2016) to use 90% CIs to test mediation and moderated mediation in multilevel modeling, as our hypotheses were directional and theory-driven.…”
Section: Analytic Strategymentioning
confidence: 99%
“…Specifically, the positive relationship between approach crafting and work engagement was stronger when coworker emotional support was high and instrumental support was low. In addition, approach crafting not only led to positive outcomes but also buffered the negative effects of job demands (Hakanen, Seppälä, & Peeters, ) and of value incongruence (Vogel, Rodell, & Lynch, ) on employee work engagement and job performance.…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
“…Indeed, people may have more influence on their own life than they think. Studies have already shown the beneficial effects of both job crafting-where employees actively reframe their work physically, cognitively, and socially (e.g., Wrzesniewski and Dutton, 2001;Demerouti, 2014;Vogt et al, 2016;Wessels et al, 2019)-and leisure crafting (Petrou and Bakker, 2016;Vogel et al, 2016;Petrou et al, 2017). A recent study by Demerouti et al (2019) suggested that the beneficial implications of job crafting transcend life boundaries, which the authors state have also consequences in terms of experiencing meaning in life.…”
Section: Introductionmentioning
confidence: 99%